Long-term performance of colorectal cancer screening programmes based on the faecal immunochemical test. Issue 12 (3rd November 2017) - Zorzi, Manuel; Hassan, Cesare; Capodaglio, Giulia; Fedato, Chiara; Montaguti, Adriana; Turrin, Anna; Rosano, Alberto; Monetti, Daniele; Stocco, Carmen; Baracco, Susanna; Russo, Francesca; Repici, Alessandro; et al.
Abstract : Background: The long-term performance of colorectal cancer (CRC) screening programmes based on a 2-year faecal immunochemical test (FIT) is still unclear. Methods: In a sample of 50 to 69-year-olds repeatedly screened with the FIT (OC-Hemodia latex agglutination test; cut-off: 20 µg haemoglobin/g faeces), we examined: (1) the FIT positivity rate, the CRC and advanced adenoma detection rate and the FIT's positive predictive value (PPV) for advanced neoplasia, at each round of screening and (2) the cumulative CRC and advanced adenoma detection rate after five rounds of FIT. Results: Over 12 years (2002–2014), 123 347 individuals were administered the FIT up to six times, and 781 CRCs and 4713 advanced adenomas were diagnosed. The CRC and advanced adenoma detection rates declined substantially from the first to the third (rate ratio (RR) 0.25, 95% CI 0.20 to 0.32) and second (RR 0.51, 95% CI 0.47 to 0.56) rounds, respectively, and then remained stable. The PPV for advanced neoplasia dropped by 18% in the second round (RR 0.82, 95% CI 0.77 to 0.89), with no further reduction thereafter due to a concomitant decline in the FIT positivity rate (RR first to sixth rounds: 0.56, 95% CI 0.53 to 0.60). The cumulative CRC and advanced adenoma detection rates over five consecutive rounds were 8.5‰ (95% CI 7.8 to 9.2), and 58.9‰ (95% CI 56.9 to 61.0), respectively. Conclusions: Repeated FIT significantly reduces the burden of colorectal disease while facilitating an efficient use of colonoscopy resources. The cumulative detection rate after five rounds of FIT is similar to primary screening with colonoscopy, supporting the need to account for the cumulative sensitivity of repeated FITs when evaluating the test's efficacy.